DAMPAK PELATIHAN PROGRAM RESCUE TERHADAP PENINGKATAN TANGGAP BENCANA PARA KADER TIM SEARCH AND RESCUE (Studi Terhadap Kader Crisis Center Fakultas Ilmu Pendidikan Universitas Negeri Jakarta) - RISA SANTOSA (Jurnal Pendidikan Luar Sekolah, 2016)
Competence disaster response should be owned by every community and students especially in Jakarta to be able to avoid both natural and non-natural disasters. Rescue training program is one way to improve the competence of students so that they can apply and disseminate to the public in the running of Tri Dharma Perguruan Tinggi, especially community service. The aim of this study was to determine , assess , and analyze and describe the phenomena that occur from the impact of the rescue program of training activities to the improvement of disaster response for cadres Crisis Center, Faculty of Education, State University of Jakarta as a Search and Rescue Team. This study used a qualitative approach with grounded theory method . Informants in this study as many as 8 people consisting of the base and source informant informant. Data collection techniques in this research is data triangulation that is combining of various data collection techniques and data sources that already exist. Results of the data obtained shows , the cadres crisi Center Faculty of Education, State University of Jakarta showed positive results , that the training program rescue that they follow is able to enhance the skills , performance and improvement against disaster response conducted by cadres Crisis Center Faculty of Education University Negeri Jakarta in activities to educate people as well as in search and rescue activities in the disaster area.